PERLINDUNGAN HUKUM ATAS MEREK ASING TERKENAL YANG BERGANTUNG PADA SISTEM KONSTITUTIF DI INDONESIA (Analisis Putusan MA No. 1300 K/ PDT.SUS-HKI/ 2017) - Muhammad Lukman Fadillah; Nahrowi Nahrowi; Ipah Farihah (JOURNAL of LEGAL RESEARCH, 2022)
Abstract      Protection every right to appear from the result the people creativity in the field of trading and industry, so improvement in the similarity of the peoples to perform passing off reputation on the other side, now therefore mark breaching especially motivated by wished for obtaining of benefit in the goods and services trading with utilized by the other mark which has been famous or popular or with the passing off owner mark or well known mark. Trading of trademark in well known mark speed on selling to the market and then certainly will obtain well benefit in the fast time. The activity unbreach of law which breach right a company known by mentioned passing off reputation.      This journal aims to find out how the legal protection of foreign brands in Indonesia against well-known marks which are foreign marks that are not registered in Indonesia in trademark registration in Indonesia, which applies the first to file system principle, in relation to the dispute over the "EIK" trademark with the "EIK, EIKA and EIKA brand".      This type of research uses a qualitative normative juridical research with a statute approach and a case approach. The statute approach in this study refers to Law Number 20 of 2016 concerning Marks and Geographical Indications, while the case approach is by examining a case that has become a court decision with permanent legal force which in this case is Supreme Court Decision Number 1300 K/Pdt.Sus-HKI/2017.      The results of this study indicate that Law Number 20 of 2016 concerning Marks and Geographical Indications only provides protection for trademark rights based on registration because it adheres to a constitutive system. The consideration of the judges of the Supreme Court in deciding the case between the EIK brand and EIK, EIKA and EIKA has given sufficient and correct consideration because it does not only refer to Law Number 20 of 2016 but also refers to the evidence in court.Key words                                      : Legal Protection, Foreign Well Known Mark, Basically The Same, Constitutive system